E-090 Experience with treatment of arteriovenous malformations of the head and neck: a focus on yakes classification and outcomes. (22nd July 2018) - Wilseck, Z; Griauzde, J; Wilkinson, D; Chaudhary, N; Pandey, A; Gemmete, J
Abstract : Purpose: To report our experience with the endovascular treatment of patients with arteriovenous malformations (AVM) of the head and neck classified utilizing the Yakes system. Methods/materials: IRB approval was obtained for this HIPAA-compliant retrospective analysis. A retrospective review of the electronic medical records of all patients who underwent endovascular treatment of a head and neck AVM between 1/1/2005 and 12/31/2017 were included in the cohort. Clinical records, operative notes, imaging, and post-operative course of patients were reviewed. The primary outcomes were clinical and angiographic treatment success rates and complications rates for lesions in each Yakes classification type. Differences in continuous variables were assessed utilizing the Wilcoxon rank sum test with significance at p<0.05. Results: A total of 29 patients were included (14 males, 15 females) with a mean age was 30.6 years. There were 0/29 (0%) Yakes type I lesions, 8/29 (28%) Yakes type IIa lesions, 5/29 (17%) Yakes type IIb lesions, 1/29 (3%) Yakes type IIIa lesions, 1/29 (3%) Yakes type IIIb lesions and 14/29 (48%) Yakes type IV lesions. Lesions were treated from an intra-arterial approach, a percutaneous approach by puncture of the nidus, and a transvenous approach with predominantly alcohol. The number of endovascular procedures was higher in the Yakes IV group than in the other groups. (W: 61 p=0.048). Excellent devascularization (>90%) was achieved in 23/29 patients (79%) including in 10/14 (71%) Yakes class IV lesions and 13/15 (87%) of the other classes. Downgrading of Schobinger clinical classification was achieved in 21/21 (100%) Schobinger class II or III patients in whom complete pre- and post-procedural clinical data was available. There were no Schobinger class IV lesions. There were a total of 5 complications in 79 procedures (6%) including 4/50 (8%) in Yakes class IV lesions and 1/29 (3%) in the other classes. Complications included skin necrosis requiring plastic surgery repair, teeth loosening requiring extraction, palatal ulceration, and a retained endovascular catheter. Conclusions: Good angiographic and clinical outcomes can be achieved in head and neck AVMs utilizing endovascular therapy with acceptable complication rates. Yakes IV lesions were more common and required an increased number of procedures and had a higher complication rate, than other Yakes subtypes. Disclosures: Z. Wilseck: None. J. Griauzde: None. D. Wilkinson: None. N. Chaudhary: None. A. Pandey: None. J. Gemmete: None.